Functional Genomic, Biochemical, and Genetic Characterization of the Salmonella pduO Gene, an ATP:Cob(I)alamin Adenosyltransferase Gene - Johnson, Celeste L. V. (American Society for Microbiology, 2001)
Salmonella enterica degrades 1,2-propanediol by a pathway dependent on coenzyme B(12) (adenosylcobalamin [AdoCb1]). Previous studies showed that 1,2-propanediol utilization (pdu) genes include those for the conversion of inactive cobalamins, such as vitamin B(12), to AdoCbl. However, the specific genes involved were not identified. Here we show that the pduO gene encodes a protein with ATP:cob(I)alamin adenosyltransferase activity. The main role of this protein is apparently the conversion of inactive cobalamins to AdoCbl for 1,2-propanediol degradation. Genetic tests showed that the function of the pduO gene was partially replaced by the cobA gene (a known ATP:corrinoid adenosyltransferase) but that optimal growth of S. enterica on 1,2-propanediol required a functional pduO gene. Growth studies showed that cobA pduO double mutants were unable to grow on 1,2-propanediol minimal medium supplemented with vitamin B(12) but were capable of growth on similar medium supplemented with AdoCbl. The pduO gene was cloned into a T7 expression vector. The PduO protein was overexpressed, partially purified, and, using an improved assay procedure, shown to have cob(I)alamin adenosyltransferase activity. Analysis of the genomic context of genes encoding PduO and related proteins indicated that particular adenosyltransferases tend to be specialized for particular AdoCbl-dependent enzymes or for the de novo synthesis of AdoCbl. Such analyses also indicated that PduO is a bifunctional enzyme. The possibility that genes of unknown function proximal to adenosyltransferase homologues represent previously unidentified AdoCbl-dependent enzymes is discussed.